Elderly Psychological Conditions in the Nursing Home Tresna Werdha (Pstw): A Study Descriptive Riau and West Sumatra Indonesia - Susanti, Nurvi; Saam, Zulfan; Nofrizal, Nofrizal; Tamal, Zahtamal; Hasrianto, Nofri (Open Access Macedonian Journal of Medical Sciences, 2021)
The aspects of emotion, memory, motivation and independence are psychological conditions that are often experienced by the elderly who live in nursing homes. experienced by the elderly who are in the nursing home environment. This study aims to describe the psychological condition of the elderly in the Husnul Khotimah Pekanbaru social home for 35 elderly and 45 elderly Sabai Nan Aluih Pariaman nursing home. This research is a descriptive survey. The research subjects were 80 elderly who were taken with the total sampling technique. Data were collected using questionnaire sheets and descriptive analysis, this study shows that the psychological condition of the elderly which includes emotional aspects of the nursing home in the second category of the Husnul Khotimah nursing home is (69%) and the Sabai Nan Aluih nursing home is 73%.(80%) in the Husnul Khotimah nursing home and 69% in the good category in the Sabai Nan Aluih nursing home. Motivational aspectat both nursing homes is in the moderate category (51%) The independence aspect is in the good category (80%) in the Husnul Khotimah nursing home while the sufficient category is 67% in the Sabai Nan Aluih nursing home. Broadly speaking, the aspects of emotion, memory, motivation are good categories, category motivation is sufficient and the category independence is good at the Husnul Khotimah nursing home and sufficient at the Sabai Nan Aluih nursing home.